Database and Knowledge Base Integration – A Data Mapping Method for Arden Syntax Knowledge Modules - Johansson, B.; Shahsavar, N.; Åhlfeldt, H.; Wigertz, O. (Methods of Information in Medicine, 1996)
One of the most important categories of decision-support systems in medicine are data driven systems where the inference engine is linked to a database. It is, therefore, important to find methods that facilitate the implementation of database queries referred to in the knowledge modules. A method is described for linking clinical databases to a knowledge base with Arden Syntax modules. The method is based on a query meta-database including templates for SQL queries which is maintained by a database administrator. During knowledge module authoring the medical expert refers only to a code in the query meta-database; no knowledge is needed about the database model or the naming of attributes and relations. The method uses standard tools, such as C++ and ODBC, which makes it possible to implement the method at many platforms and to link to different clinical databases in a standardized way.
Keywords: Database and Knowledge-base Integration; Decision Support Systems; Arden Syntax; Medical Logic Modules; SQL